2013
DOI: 10.1097/sla.0b013e318269d03b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Robotic Surgery on Sexual and Urinary Functions After Fully Robotic Nerve-Sparing Total Mesorectal Excision for Rectal Cancer

Abstract: RTME allows for preservation of urinary and sexual functions. This is probably due to the superior movements of the wristed instruments that facilitate fine dissection, coupled with a stable and magnified view that helps in recognizing the inferior hypogastric plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 30 publications
8
111
0
2
Order By: Relevance
“…To some degree, NA chemotherapy alone could replace NA CRT as a rectal cancer treatment for men, which would reduce the effect on erectile and urinary function. Although the erectile and urinary dysfunction after rectal cancer treatment has been investigated [16][17][18], to our knowledge, this study is the first to address differences in erectile and urinary dysfunction between NA CRT and NA chemotherapy alone in men treated for rectal cancer.…”
Section: Discussionmentioning
confidence: 94%
“…To some degree, NA chemotherapy alone could replace NA CRT as a rectal cancer treatment for men, which would reduce the effect on erectile and urinary function. Although the erectile and urinary dysfunction after rectal cancer treatment has been investigated [16][17][18], to our knowledge, this study is the first to address differences in erectile and urinary dysfunction between NA CRT and NA chemotherapy alone in men treated for rectal cancer.…”
Section: Discussionmentioning
confidence: 94%
“…However, the literature does consistently reveal similar short-term outcomes with longer operative times and higher costs [113,114]. Some early studies have shown trends toward better sexual or bladder function; nevertheless, this has not reached significance and has yet to be proven [115,116]. Currently, randomized control trials are looking to answer these and other questions regarding the widespread role of robotic surgery for rectal cancer [117].…”
Section: Colorectal Surgerymentioning
confidence: 86%
“…The results reported by McGlone et al (23) are significantly favorable to the minimally invasive approach; the authors emphasised the advantages afforded by laparoscopy for the preservation of pelvic function. In a multicentre study (21) , the results of robotic surgery were comparable to those of laparoscopic surgery or laparotomy, and robotic surgery was associated with low rates of urinary and sexual dysfunction. In the present study, no significant difference was found between the surgical approaches, neither of which behaved as a risk factor for postoperative urinary dysfunction.…”
Section: Discussionmentioning
confidence: 89%